Pengaruh Fear Of Missing Out (FoMO), Brand Image, dan Promosi Sosial Media Terhadap Keputusan Pembelian (Studi Kasus Pada Tiket Konser Blackpink di Indonesia Tahun 2023) - Cindy Aprillia Azhary; Nora Andira Brabo; Heni Iswati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research aims to analyze the influence of Fear of Missing Out (FoMO), Brand Image, and Social Media Promotion on Purchasing Decisions (Case Study of Blackpink Concert Tickets in Indonesia in 2023). This research used a survey method with a sample of 170 people using a purposive sampling technique. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique uses the SPSS 26.0 application by means of multiple linear regression analysis, autocorrelation analysis and determination analysis. The research results provide conclusions: (1) Fear of Missing Out (FoMO) has no effect on purchasing decisions; (2) Brand Image has a positive and significant effect on Purchasing Decisions; (3) Social Media Promotion has a positive and significant effect on Purchasing Decisions; (4) Fear of Missing Out (FoMO), Brand Image, and Social Media Promotion have a positive and significant effect on Purchasing Decisions.